PENERAPAN MODEL INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK - Jayantri, Ysiyar (LPPM STKIP PGRI Bandar Lampung, 2019)
The problem of this research is motivated by the lack of optimal thematic learning outcomes of class IV students of Negeri 3 Talang Elementary School. The purpose of this study was to know the improvement of student learning outcomes through the application of the inquiry learning model. The research method used is classroom action research (PTK) which is carried out in 2 cycles, each cycle consisting of the stages of planning, implementation, observation, and reflection. The technique of collecting data is done by observation and test questions. The analysis technique used is qualitative and quantitative analysis. The results of the study show that through the application of the inquiry model can improve the thematic learning outcomes of students. This can be seen from the percentage of classical completeness in student learning outcomes in the first cycle is (67%) obtained by the category